Cassava (Manihot Esculenta Crantz) Processing as Enbal to Support Food Security in Wab Village, Hoat Sorbay Subdistrict, Southeast Maluku Regency - Riry, Robert Berthy; Rahakratat, Giliant; Manakane, Susan Evelin (JENDELA PENGETAHUAN, 2024)
This study aims to explore the process of processing cassava (Manihot esculenta Crantz) into enbal and its contribution to food security among the community in Wab Village, Hoat Sorbay District, Southeast Maluku Regency. The method used is qualitative, with data collection techniques through observation, interviews, documentation, and questionnaires. The results of the study indicate that the cassava processing process involves several stages, from cleaning, rinsing, grating, pressing, to air-drying. Farmers use simple tools and traditional methods passed down through generations. The processed cassava is stored in open places such as trays and sieves (Sivat) and is immediately processed to prevent spoilage and mold. The quick and efficient production of enbal helps maintain the quality and taste of the final product. The study also found that the abundance of cassava in farmers' fields ensures a stable supply of food reserves, reduces dependence on external food sources, and supports the economic stability of farmers' families. In conclusion, the cassava processing method into enbal applied by farmers in Wab Village not only supports local food security but also strengthens the local economy through optimal and sustainable utilization of local resources.